Right to Development in Securitized Environments: A Theoretical Approach - Guerrero, Efrén (2024)
One of the phenomena that have marked the reality of states in the last two years is the navigation through a series of crises derived from the post-pandemic scenario: the increase in poverty, the decrease in state capacities to address the needs of a vulnerable and affected population, as well as the increase in the cost of living and a growing sense of insecurity. Currently, the term "failed states" has been used in the Ecuadorian case regarding events related to the infiltration of organised crime into the state structure. In this context of a volatile, uncertain, and ambiguous world, political science and constitutional law face the need to re-evaluate their foundations and recognize the importance of establishing civilizing pacts to manage conflicts and strengthen trust in the state. This paper aims to propose lines of argument, using the Ecuadorian example, in the field of constitutional law that make it possible to: a) show how the right to development is limited by securitization and discursive emptying in favour of public order; b) how it affects the idea of the construction of integral development dynamics. It is also concluded that, given the existence of interconnected threats and coordinated actors, human development becomes a fundamental need in public management.